1993
DOI: 10.1029/93wr01286
|View full text |Cite
|
Sign up to set email alerts
|

Channeling and Fickian Dispersion in fractal simulated porous media

Abstract: We simulate tracer transport in a two-dimensional porous medium. We provide justification for the use of a fractal scaling law to characterize the spatial variability of rock properties, leading to a fractal rock property model. A methodology based on the fractal model discussed is applied to experimental data to generate a "fracta! porous medium" and to solve the associated flow and tracer transport problems. Tracer breakthrough curves are computed for three different breakthrough distances. An advection-disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…However, Neuman 's [1990] estimate of H (his ω) based on using ln K fBm to explain the observed scale dependence of apparent dispersivity was 0.25. When the Molz and Boman [1993] data were reanalyzed assuming that the vertical variation of ln( K ) was represented by the nonstationary function fBm [ Molz and Boman , 1995], the resulting Hurst coefficient was around 0.3, implying negative correlation of the ln K increments, reasonably consistent with the Neuman [1990] ln K result and the porosity result ( H = 0.34) of Grindrod and Impey [1993]. Early work by Kemblowski and Chang [1993] using relatively small data sets resulted in fBm‐based H values in the vertical and horizontal directions of 0.18 and 0.53, respectively.…”
Section: Fractals and Multifractals In Subsurface Hydrologymentioning
confidence: 66%
“…However, Neuman 's [1990] estimate of H (his ω) based on using ln K fBm to explain the observed scale dependence of apparent dispersivity was 0.25. When the Molz and Boman [1993] data were reanalyzed assuming that the vertical variation of ln( K ) was represented by the nonstationary function fBm [ Molz and Boman , 1995], the resulting Hurst coefficient was around 0.3, implying negative correlation of the ln K increments, reasonably consistent with the Neuman [1990] ln K result and the porosity result ( H = 0.34) of Grindrod and Impey [1993]. Early work by Kemblowski and Chang [1993] using relatively small data sets resulted in fBm‐based H values in the vertical and horizontal directions of 0.18 and 0.53, respectively.…”
Section: Fractals and Multifractals In Subsurface Hydrologymentioning
confidence: 66%
“…The influence of aperture variability on flow and solute transport in two-dimensional fissures is evident in several numerical simulation studies [e.g., Brown, 1987;Moreno et al, 1988;Tsang and Tsang, 1989;Grindrod and Impey, 1993] and has been characterized theoretically [e.g., Gelhar, 1987Gelhar, , 1993. In particular, significant flow channeling is evident in these numerical simulation studies.…”
Section: Introductionmentioning
confidence: 99%
“…The change of type of diffusion may not necessarily be related to the scale. Grinrod and Impey (1993) simulated solute transport in saturated two-dimensional fractal porous medium and found that at early stages an anomalous transport occurs, whereas the later breakthrough is predominantly Fickian. Changes of the diffusivity scaling as the water transport in soil progresses seem to be an interesting issue to explore.…”
Section: Resultsmentioning
confidence: 99%